2016
DOI: 10.1016/s0140-6736(15)01168-x
|View full text |Cite
|
Sign up to set email alerts
|

Anastrozole versus tamoxifen in postmenopausal women with ductal carcinoma in situ undergoing lumpectomy plus radiotherapy (NSABP B-35): a randomised, double-blind, phase 3 clinical trial

Abstract: Background NSABP B-35 is a phase III trial comparing anastrozole (A) to tamoxifen (T) for breast cancer-free interval (BCFI), defined as time from randomization to any breast cancer event: local, regional, distant, or contralateral, invasive or DCIS. Methods Postmenopausal women with hormone-positive DCIS treated by lumpectomy with clear resection margins and whole breast irradiation were randomized to receive either 20mg/day T or 1mg/day A (blinded) for 5 years. Stratification was by <60 versus ≥60 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
127
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 10 publications
1
127
2
6
Order By: Relevance
“…In 2000, tamoxifen, a selective estrogen receptor modulator (SERM), has gained approval by the Food and Drug Administration (FDA) to be used as an adjuvant endocrine therapy in DCIS patients (8). This was based on the first of the several clinical trials that have suggested potential benefits of endocrine therapy in cases of DCIS, the National Surgical Adjuvant Breast and Bowel Project NSABP B-24 trial (8)(9)(10)(11)(12). NSABP B-24 (8) was double-blinded, randomized, controlled trial enrolling 1804 DCIS patients who had previously undergone breast conserving surgery and whole breast radiotherapy.…”
Section: Adjuvant Endocrine Therapy and Clinical Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…In 2000, tamoxifen, a selective estrogen receptor modulator (SERM), has gained approval by the Food and Drug Administration (FDA) to be used as an adjuvant endocrine therapy in DCIS patients (8). This was based on the first of the several clinical trials that have suggested potential benefits of endocrine therapy in cases of DCIS, the National Surgical Adjuvant Breast and Bowel Project NSABP B-24 trial (8)(9)(10)(11)(12). NSABP B-24 (8) was double-blinded, randomized, controlled trial enrolling 1804 DCIS patients who had previously undergone breast conserving surgery and whole breast radiotherapy.…”
Section: Adjuvant Endocrine Therapy and Clinical Outcomementioning
confidence: 99%
“…Nonetheless, tamoxifen had no apparent benefit among the cohort of patients who received radiotherapy (13). In view of the recent evidence that aromatase inhibitors are superior to tamoxifen in the treatment of postmenopausal women with ER positive invasive breast cancers (14), two large, double-blinded, randomized clinical trials were carried out to compare the performance of anastrozole versus tamoxifen in the adjuvant management of hormone-receptor positive, postmenopausal women with DCIS (11,12). In the NSABP b-35 trial (12), 3104 DCIS patients with established clear surgical margins after breast conserving surgery and radiotherapy were enrolled in this study and randomized into either tamoxifen or anastrozole treatment arms.…”
Section: Adjuvant Endocrine Therapy and Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании комплексного взаимодействия биомаркеров и визуализации IBIS-II (Integrated Biomarkers and Imaging Study II) [19] и проекте NSABP В-35 [20] оценена роль ингибиторов ароматазы (анастрозола) у постменопаузальных больных DCIS, которым проводили сохранные операции с ЛТ или без нее. Цель исследований -определить проме-жуток времени от момента рандомизации до выявле-ния рака (рецидива или нового случая) и оценить общую выживаемость и качество жизни (см.…”
unclassified
“…Однако преимущество анастрозола зарегистрировано только у больных в пост-менопаузе моложе 60 лет [20]. Не выявлено существен-ного влияния гормонотерапии на риск развития инвази-вого рака в ипсилатеральной молочной железе, однако зарегистрировано снижение данного риска в контрлате-ральной железе с наибольшей достоверностью в группе анастрозола.…”
unclassified